3D characterisation of debris clouds under hypervelocity impact with large-field pulsed digital in-line holography. (August 2021) - Xue, Zhi-liang; Xie, Ai-min; Zhu, You-qi; Zhong, Yun-hao; Wu, Ying-chun; Zhou, Yong-gang; Wu, Xue-cheng
Highlights: A model for the large-field pulsed digital in-line holography system is developed. The hologram of debris clouds under hypervelocity impact is clearly captured. 3D characterisation, debris shape and particle size of debris clouds are determined. Abstract: To expand the field of view and obtain a full-scale image of a debris cloud, a large-field pulsed digital in-line holography (DIH) system is developed to study the three-dimensional (3D) positions and shapes of debris clouds generated by hypervelocity impact. A general model for the large-field pulsed DIH system is introduced. Derived from strict theoretical analysis, it suggests that the hologram recorded by a large-field pulsed DIH system can be described by an equivalent lensless system. At the Hypervelocity Impact Research Centre of the China Aerodynamics Research and Development Centre, based on hypervelocity impact equipment with a 7.6 mm bore, experiments on a 3 mm aluminium sphere impacting a 1 mm thick aluminium target plate with a velocity of 3.58 km/s were carried out. Ensuring the successful capture of the transient state of debris clouds, the large-field pulsed DIH system is synchronised with the impact event and the combination of the neutral density filter and the bandpass filter is proposed, to eliminate the plasma radiation and enhance the signal-to-noise ratio of the hologram. The experimental results show that the holographic fringes are clearly recorded and the detailed shapes and structures of both large and small aluminium fragments are observed after reconstruction. The structure of debris clouds can be divided into three parts: front, core and shell, agreeing well with results measured by laser shadowgraph. The study demonstrates the feasibility of a large-field pulsed DIH system for accurate measurements of ultrafast debris clouds and shows great potential in the diagnostics of hypervelocity impacts.